2018
DOI: 10.2135/cropsci2017.06.0375
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Function of Cover Crops Interseeded into Corn

Abstract: Cover crops can provide ecological services and improve the resilience of annual cropping systems; however, cover crop use is low in corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] rotations in the upper Midwest due to challenges with establishment. Our objective was to compare three planting methods to establish cover crops (winter rye [Secale cereale L. ‘Rymin’], red clover [Trifolium pretense L. ‘Medium’], hairy vetch [Vicia villosa Roth], field pennycress [Thlaspi arvense L. ‘MN‐106’], and a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 39 publications
8
117
2
Order By: Relevance
“…It was evident that cover crops were not competitive with corn or summer annual weeds at the densities established at our research sites. Our research used broadcast interseeders, which results in lower densities of cover crops compared with drilled interseeders (Noland et al., ). Further research is necessary to explore the competitiveness of higher densities of cover crops seeded from V2–V5 in corn, since annual ryegrass drill interseeded prior to V4 produced over 1500 kg ha −1 , nine times greater than average biomass production in our research, and reduced corn grain yield (Curran et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was evident that cover crops were not competitive with corn or summer annual weeds at the densities established at our research sites. Our research used broadcast interseeders, which results in lower densities of cover crops compared with drilled interseeders (Noland et al., ). Further research is necessary to explore the competitiveness of higher densities of cover crops seeded from V2–V5 in corn, since annual ryegrass drill interseeded prior to V4 produced over 1500 kg ha −1 , nine times greater than average biomass production in our research, and reduced corn grain yield (Curran et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…and crimson clover seeded as a single species and in mixtures (Abdin et al., , ; Belfry & Van Eerd, ; Caswell, Wallace, Curran, Mirsky, & Ryan, ; Curran et al., ; Grabber, Jokela, & Lauer, ; Scott, Mt. Pleasant, Burt, & Otis, ; Youngerman, DiTommaso, Curran, Mirsky, & Ryan, ; Zhou, Madramootoo, MacKenzie, Kaluli, & Smith, ), and oilseed radish ( Raphanus sativus L.) interseeded as a single species in Pennsylvania and Ontario, Canada (Belfry & Van Eerd, ; Roth, Curran, Wallace, Ryan, & Mirsky, ) and in a mixture in Minnesota (Noland et al., )…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review by Tonitto et al (2006) reported a 10% reduction in grain yield of primary crops under legume cover crops. Noland et al (2018) found that to reduce soil NO 3 while maintaining corn and subsequent soybean yields, cover crops should be inter-seeded into corn at the seven-leaf collar stage. Dozier, Behnke, Davis, Nafziger, and Villamil (2017) and Marcillo and Miguez (2017) found non-legume cover crops had no effects on the grain yield of corn, especially in the short term.…”
Section: Impacts Of Cover Crops (Legume Nonlegume and Legume-non-lmentioning
confidence: 99%